Between Diffusion and Propaganda: Latin Literature trhough Postage Stamps (Minerva, 2019)
This paper reviews those philatelic issues which many countries, mostly European, have given over to Latin Literature. It also studies the different pieces from several points of view, the philological on the one hand, the archaelogical and artistic on the other. Most of all, it tries to clarify whether those stamps dedicated to Latin Literature are neutral or not from the viewpoint of the messages they transmit, reaching the conclusion that most of them have just a conmemorative purpose, but others pursue different objectives, including political propaganda.
Keywords: Latin Literature; stamps; propaganda; archaeology